Management Strategy to Improve Teacher Professionalism Competence in Private Madrasah Aliyah - Eko Budi Prasetyo; Badrudin Badrudin; Qiqi Yuliati Zakiyah; Dian Dian (Yayasan Azka Hafidz Maulana, 2026)
This research is since many teachers experience obstacles in pedagogical and professional aspects, such as lack of mastery of material, innovative learning methods, and continuous self-development. These data indicate that in general, the professional competence of teachers in private Islamic senior high schools is still in the low to adequate category, because only a small proportion of teachers meet the expected competency standards. The purpose of this study was to determine the strategic management of improving teacher professional competence in private Islamic senior high schools. The research approach used in this study was a qualitative approach. The results showed that strategic management carried out systematically and planned can improve the pedagogical competence, personality, and professionalism of teachers. In addition, the commitment of madrasah management in developing the quality of teaching staff also contributes to improving the quality of learning and the overall success of the madrasah. Appropriate and effective management strategies are the main key in encouraging teachers to continue to develop and innovate according to the needs of the times. Thus, the implementation of good strategic management not only improves the professional competence of teachers, but also has a positive impact on the quality of education at Madrasah Aliyah Aliyah Al Muhajirin and Minhajul Haq Purwakarta, so that they are able to compete and meet national and international education standards.